Caracterização clínica, composição corporal e história natural de lipodistrofias genéticas - Lima, Grayce Ellen Cruz Paiva (2024)
Genetic lipodystrophies (GL) constitute a rare group of disorders associated with severe metabolic complications. The scarcity of data on the natural history of these diseases, especially in the Brazilian context, highlights the need for comprehensive studies. Phenotypic characteristics play a crucial role in the diagnosis of GL. The aim of this study was to compare the clinical features, body composition, and natural history of GL (congenital generalized lipodystrophy - CGL - and familial partial lipodystrophy - FPL) and to establish cutoff points for body composition measures that could aid in clinical screening and diagnosis. This cross-sectional study was conducted at the Diabetes, Dyslipidemia, and Metabolic Syndrome outpatient clinic of the Federal University of Ceará/EBSERH, from May 2022 to October 2023. Clinical, body composition, laboratory, and imaging data were collected from patients with a confirmed diagnosis of GL by genetic testing, and control groups matched by gender, age, and body mass index were selected for comparison of body composition measures. A total of 62 GL patients (29 with CGL and 33 with FPL) were included. The majority were women (69%). The mean age was 32 ± 18 years, ranging from 2 to 68 years, and was lower in the CGL subtype (22 ± 12 years). Liver disease was the most common complication, observed in 83% of cases (72% in CGL and 100% in FPL). The prevalence of diabetes mellitus (DM) was 70% (79% in CGL and 61% in FPL). Peripheral neuropathy (PN) occurred in 64% of DM patients (61% in CGL and 68% in FPL), followed by nephropathy in 49% (57% in CGL and 39% in FPL) and retinopathy in 33% (48% in CGL and 13% in FPL). Cardiomyopathy occurred in 63% of patients (74% in CGL and 43% in FPL). Age at diagnosis was lower in CGL for all outcomes. Since the beginning of follow-up, five patients with CGL have died, whereas no FPL patients have died. Body composition analysis revealed differences between CGL and FPL patients in all parameters assessed by skinfold thickness (SF) and dual-energy X-ray absorptiometry (DXA), except for calf SF, which was similar between the two subtypes. The ROC curve allowed for the establishment of cutoff points (8 mm for calf SF, 15 mm for thigh SF, and 23.2% for percentage of fat in the legs - PFL) with good accuracy in screening and clinical diagnosis of GL. This study covered a wide range of GL and revealed a high prevalence of liver disease, DM, PN, nephropathy, retinopathy, and cardiomyopathy. For all these morbid outcomes, the age of diagnosis was lower in CGL. Adverse progressions such as infections and cirrhosis led to early death, especially in CGL. New cutoff points for thigh SF and PFL were identified with high accuracy. Uniquely, a cutoff point for calf SF was also established, suggesting this parameter as useful for screening and clinical diagnosis of GL.